Preparation method of electronic-grade high-purity boric acid

CN123002870APending Publication Date: 2026-10-30HEBEI SHOUYOU MEDICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611469562.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

这些方法在提高主含量、降低部分金属杂质方面取得了一定效果,但普遍存在纯化效果有限、能耗较高、流程复杂以及易引入新的离子型或有机杂质等问题;特别是在多次溶解与重结晶过程中,母液中的杂质仍可能被再次包裹进入新生晶体,难以在工业尺度上稳定获得电子级所需的极低杂质水平

Benefits of technology

[0026]本发明将高纯度硼酸制备过程中如何分离杂质的主要问题,由传统的溶液化学分离转化为了熔体偏析、区熔与水化残渣富集的方式。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002870A_ABST
    Figure CN123002870A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of high-purity boric acid production, and discloses a preparation method of electronic-grade high-purity boric acid, which comprises the following steps: industrial-grade boric acid is dehydrated and decomposed into a boric oxide melt in a multi-temperature-zone tubular furnace in stages, the boric oxide melt is directionally solidified under an inert atmosphere to obtain a boric oxide ingot, the boric oxide ingot is refined by reciprocating zone melting in a narrow melting zone in a zone melting furnace for multiple times, the middle section high-purity boric oxide is cut off, and then the high-purity boric oxide is crushed and placed in a spraying water reaction device, and the high-purity boric oxide is watered layer by layer under the condition of controlling temperature and flow and circulating the incompletely watered particles to obtain a high-purity boric acid solution, and the high-purity boric acid solution is prepared into electronic-grade high-purity boric acid with extremely low metal impurity content through slow cooling crystallization, solid-liquid separation, low-temperature washing and vacuum drying. Through solid-phase zone melting refining of boric oxide combined with controlled hydration and slow cooling crystallization, the present application realizes deep migration and cutting of metal and difficult-to-volatilize impurities, avoids the problems of traditional wet wrapping and repeated pollution, and can stably obtain ultra-high-purity boric acid products meeting the requirements of electronic grade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of high-purity boric acid production technology, and more specifically, to a method for preparing electronic-grade high-purity boric acid. Background Technology

[0002] Boric acid, as a basic boron source, is widely used in glass manufacturing, electronics, pharmaceuticals, military, nuclear power, and aerospace. With the development of high-tech industries such as integrated circuits, optoelectronic devices, and precision optical materials, the purity of boric acid has been further increased from ordinary high-purity grades to nuclear power and electronic grades. This not only requires the main boron content to reach 99.99% or even higher, but also demands that the content of metallic impurities such as Ca, Fe, and Pb, as well as anionic impurities such as sulfate, chloride, and nitrate, be reduced to ppm or even ppb levels.

[0003] However, existing domestically produced industrial boric acid is usually prepared by wet processes such as sulfuric acid method, hydrochloric acid method, and ammonia carbonate method. Although the main content can reach more than 95%, it often contains water-insoluble matter and a variety of soluble salt impurities, including metal oxides, metal carbonates, metal sulfides, and various acid radicals related to the process. These impurities are small and highly dispersed, and they are easily encapsulated inside the crystal as crystal nuclei during the boric acid crystallization process. It is difficult to completely remove them by simply relying on conventional dissolution and crystallization processes.

[0004] For the purification of industrial boric acid, various process routes have been proposed in the existing technology, including multi-stage recrystallization, ion exchange, esterification-distillation-hydrolysis, electrochemical and permeation membrane methods, complexation masking recrystallization, chelation adsorption, extraction, and combinations of multiple methods. These methods have achieved certain results in increasing the main content and reducing some metal impurities, but they generally suffer from limited purification effect, high energy consumption, complex processes, and easy introduction of new ionic or organic impurities. In particular, during multiple dissolution and recrystallization processes, impurities in the mother liquor may still be re-encapsulated into the new crystals, making it difficult to stably obtain the extremely low impurity levels required for electronic grades on an industrial scale.

[0005] For processes targeting high-purity boric acid for nuclear power or photovoltaic applications, the usual method still involves repeated conversion and pH adjustment in an aqueous solution system, along with the use of conversion aids, complexing agents, or ion exchange resins for purification. Although this can reduce the content of some metals and anions to 1×10⁻⁶, the process is still characterized by the following steps: -5 While the scale is large, it still mainly relies on multi-stage wet chemical processes. Further reduction of trace impurities such as alkali metals and alkaline earth metals is constrained by factors such as crystallization embedding, secondary resin pollution, and organic residues.

[0006] Therefore, starting from industrial-grade boric acid with an impurity level of only 95% to 99.5%, further reducing the content of metal and anionic impurities, especially effectively controlling Ca, Na ions and difficult-to-remove trace metals, without excessively increasing process complexity and reagent types, to obtain high-purity boric acid products that meet the requirements of electronic applications, while taking into account process stability, scalability, and control of impurity introduction risks, remains a technical problem to be solved in this field. Summary of the Invention

[0007] The purpose of this invention is to provide a method for preparing electronic-grade high-purity boric acid to solve the above-mentioned problems.

[0008] To achieve the above objectives, the present invention provides the following solution:

[0009] A method for preparing electronic-grade high-purity boric acid includes the following steps:

[0010] (1) Industrial grade boric acid is heated in a tube furnace with multiple temperature zones. Free water is removed in the first temperature zone at 80-140℃, dehydration is carried out in stages in the second temperature zone at 140℃-220℃, and the temperature is maintained in the third temperature zone at 220℃-360℃ for 2-8 hours to obtain boron trioxide melt.

[0011] (2) The boron trioxide melt is poured into a crystallization mold with a horizontal temperature gradient under an inert atmosphere and cooled directionally from one end to the other to obtain a boron trioxide ingot.

[0012] (3) Place the boron trioxide ingot in a vertically arranged zone melting furnace, and form a narrow melting zone in the ingot by a ring heater that moves back and forth along the ingot axis. Move the melting zone from one end of the ingot to the other end at a speed of 0.5-10 mm / min to complete 2-10 reciprocating zone melting refining to obtain the high-purity boron trioxide mid-section after zone melting refining.

[0013] (4) The high-purity boron trioxide middle section is crushed into particles with a particle size of 0.5-10 mm and added to a hydration reactor with an internal surface spray structure. Under the condition of 30-80℃, high-purity water is sprayed, the hydration reaction time is controlled to be 1-10 hours, and the boric acid concentration in the solution is controlled to be saturated by adjusting the spray flow rate and hydration temperature, so as to obtain a mixed system of high-purity boric acid solution and incompletely hydrated particles;

[0014] (5) Perform solid-liquid separation on the mixed system formed in step (4), recover the high-purity boric acid solution, return the incompletely hydrated boron trioxide particles to step (4) for further hydration until the residual rate is lower than the predetermined mass fraction, and combine the high-purity boric acid solutions obtained from multiple cycles to obtain the target high-purity boric acid solution.

[0015] (6) The high-purity boric acid solution is slowly cooled and crystallized under stirring. The final cooling temperature is controlled at 5℃-25℃. Boric acid crystals are precipitated, separated by centrifugation or filtration, and then quickly washed with high-purity water. The solution is then vacuum dried at 50℃-80℃ to obtain electronic-grade high-purity boric acid product.

[0016] Furthermore, the industrial-grade boric acid in step (1) contains 95% to 99.5% H3BO3 by mass.

[0017] Furthermore, in step (1), the temperature control of each temperature zone of the tubular furnace is as follows: the temperature of the first temperature zone is 90-120℃, the temperature of the second temperature zone is 150-190℃, and the temperature of the third temperature zone is 260-320℃, and step (1) is carried out under the protection of argon or nitrogen.

[0018] Furthermore, in step (2), the crystallization mold is made of stainless steel or high-purity quartz with polished inner wall, and the ratio of mold length to diameter is 5-20:1. During directional cooling, a cold end is set at the bottom of the mold and a hot end is set at the top of the mold, so that the solid-liquid interface is pushed unidirectionally from the bottom to the top of the mold.

[0019] Furthermore, in step (3), the zone melting refining process is carried out under a low-pressure inert atmosphere, and the pressure inside the zone melting furnace is controlled at 10-90 kPa.

[0020] Furthermore, the number of reciprocating cycles in the zone melting refining in step (3) is set according to the initial content of metal impurities in the industrial-grade boric acid. For raw materials with a metal impurity mass fraction in the range of 100-1000 μg / g, the number of reciprocating cycles in the zone melting is 4-8 times.

[0021] Furthermore, the residual rate of incompletely hydrated boron trioxide particles in step (5) is determined by online quality monitoring or intermittent sampling and weighing. When the mass fraction of residual boron trioxide is less than 1% of the initial amount added, the cyclic hydration of the current batch of particles is stopped.

[0022] Furthermore, in step (6), the slow cooling crystallization adopts a staged cooling method. First, the temperature is lowered to near the saturation temperature at a rate of 1℃-3℃ per hour in the range above the saturation temperature of boric acid, and then lowered to the final temperature at a rate of 0.2-1℃ per hour. At the beginning of the cooling, 0.1-1.0% of high-purity boric acid crystals by mass of the solution are added as seed crystals.

[0023] Furthermore, in step (6), the high-purity water used for washing is low-temperature high-purity water, and the washing water temperature is controlled at 5-15℃. The volume of washing water for each batch of boric acid crystals is 0.5-3 times the volume of the crystals.

[0024] On the other hand, the present invention also protects high-purity boric acid obtained by the above-described method for preparing electronic-grade high-purity boric acid.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0026] This invention addresses the key issue of separating impurities during the preparation of high-purity boric acid by transforming traditional solution chemical separation into a method involving melt segregation, zone melting, and enrichment of hydration residues.

[0027] Specifically, by completely decomposing industrial-grade boric acid into boron trioxide melt in a multi-zone tubular furnace, and then subjecting the boron trioxide melt to directional solidification and multiple zone refining processes, boric acid crystals are regenerated under conditions of high-purity water spray hydration and slow cooling crystallization. This achieves deep migration and enrichment removal of metallic impurities and non-volatile impurities in a solid-melt state, avoiding the problem of impurities repeatedly circulating and encapsulating between solution and crystals in traditional wet purification. This allows for the efficient removal of elements such as Ca, Na, Fe, and Pb. At the same time, the hydration and crystallization steps only introduce high-purity water as a single medium, significantly reducing the risk of introducing ionic and organic residues. Thus, with a relatively simple and scalable process flow, high-purity boric acid products that meet the requirements of electronic applications can be obtained. Attached Figure Description

[0028] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 This is a flowchart illustrating a method for preparing electronic-grade high-purity boric acid, as provided in an embodiment of the present invention. Detailed Implementation

[0030] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0031] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0032] See Figure 1 As shown, this embodiment of the invention provides a method for preparing electronic-grade high-purity boric acid, comprising:

[0033] First, in step (1), the solid-phase decomposition and oxide preparation steps are as follows: Industrial-grade boric acid is fed into a tube furnace with multiple temperature zones and heated sequentially. Free water is removed by controlling the temperature at 80-140℃ in the first temperature zone, dehydration is carried out in stages by controlling the temperature at 140-220℃ in the second temperature zone, and the temperature is controlled at 220-360℃ in the third temperature zone and maintained for 2-8 hours. This allows the industrial-grade boric acid to gradually complete the removal of crystal water and structural decomposition, ultimately transforming it completely into boron trioxide melt. At the same time, water vapor and volatile impurities generated during decomposition are continuously discharged under an inert or reduced pressure atmosphere to reduce the residual volatile impurities other than metal oxides and to avoid the introduction of new metal contamination from the external atmosphere.

[0034] Step (2) Ingot forming step: The boron trioxide melt is poured into a crystallization mold with a horizontal temperature gradient under the protection of an inert atmosphere. It is directionally cooled from one end to the other. The boron trioxide solidifies sequentially along the length of the mold to form a boron trioxide ingot with a single solid-liquid interface propagation direction, providing a regular ingot shape and controllable solidification direction for subsequent zone melting refining.

[0035] Subsequently, in step (3) zone melting refining: the boron trioxide ingot is placed in a vertically arranged zone melting furnace, and a narrow melting zone is formed inside the ingot by a ring heater that moves back and forth along the ingot axis. The melting zone is moved back and forth between the two ends of the ingot 2-10 times at a speed of 0.5-10 mm / min. During the zone melting process, impurities accumulate in the melting zone at the solid-liquid interface according to the distribution coefficient, and after multiple reciprocations, they are mainly concentrated at the two ends of the ingot. The zone melting refining process is carried out under a low-pressure inert atmosphere of 10-90 kPa, which on the one hand, simultaneously removes the residual volatile impurities generated or released during the zone melting process, and on the other hand, reduces the re-adsorption of impurities in the external atmosphere by the melting zone. After zone melting, the impurity-rich sections at both ends of the ingot are removed, leaving only the middle section with higher purity, to obtain the high-purity boron trioxide middle section refined by zone melting. The number of zone melting cycles is set to 4-8 times according to the different levels of metal impurity mass fraction in industrial-grade boric acid raw materials within the range of 100-1000 μg / g. The termination position of the molten zone is recorded after each zone melting cycle to optimize the removal length.

[0036] Next, in step (4), the controlled hydration step is performed: the high-purity boron trioxide mid-section is crushed into particles with a diameter of 0.5-10 mm and loaded into a hydration reactor equipped with an internal surface spray structure. Within the temperature range of 30-80℃, high-purity water is sprayed onto the boron trioxide particles from top to bottom, controlling the hydration reaction time to 1-10 hours. This allows the boron trioxide to hydrate layer by layer on the particle surface and gradually dissolve to generate boric acid. Simultaneously, the solution conductivity or refractive index is monitored online, and the spray flow rate and hydration temperature are adjusted accordingly to ensure that the boric acid concentration in the solution remains close to saturation without significant spontaneous crystallization, thus forming a mixed system composed of high-purity boric acid solution and incompletely hydrated particles. The conductivity and refractive index of the effluent are detected in real time by an online conductivity meter and refractive index sensor installed on the effluent pipeline. The concentration-conductivity calibration curve and concentration-refractive index calibration curve of the boric acid solution are determined in advance within the temperature range of 30℃ to 80℃. At the current hydration temperature, the conductivity and refractive index values ​​corresponding to 90% to 95% of the saturated solubility of boric acid at that temperature are determined as the upper limit values ​​for control. When the real-time detected effluent conductivity is greater than or equal to the upper limit value of conductivity, or the real-time detected effluent refractive index is greater than or equal to the upper limit value of refractive index, the control system automatically reduces the spray flow rate from 2 BV / h to 1 BV / h. When the boric acid mass concentration corresponding to the conductivity and refractive index falls back to the range of 85% to 90% of the saturated solubility, the spray flow rate is restored to 2 BV / h.

[0037] Step (5) Solid-liquid separation and recycling: The above-mentioned mixed system is subjected to solid-liquid separation to recover the high-purity boric acid solution. The incompletely hydrated boron trioxide particles are returned to the hydration reactor for further hydration. The mass ratio of residual boron trioxide is determined by online quality monitoring or intermittent sampling and weighing. When the mass fraction of residual boron trioxide to the initial addition amount decreases to below 1%, the recycling and hydration of the current batch of particles is stopped, thereby ensuring that most of the boron trioxide is converted into boric acid in solution form, while undissolved or sparingly soluble impurities are retained in the solid residue as much as possible. The high-purity boric acid solutions obtained from multiple cycles are combined to obtain the target high-purity boric acid solution, providing a stable precursor for the crystallization step.

[0038] Finally, step (6) crystallization and drying: The high-purity boric acid solution is slowly cooled and crystallized under stirring according to a preset cooling curve. Specifically, the solution is first cooled to near the saturation temperature at a rate of 1-3°C per hour within a range above the boric acid saturation temperature, and then cooled further at a rate of 0.2-1°C per hour to a final temperature of 5-25°C. At the beginning of the cooling stage, 0.1%-1.0% of high-purity boric acid crystals by mass of the solution are added as seed crystals to guide the boric acid crystals to grow in a regular manner, reducing impurity inclusions and crystal defects. After crystallization, the boric acid crystals are separated by centrifugation or filtration. The crystals are then rapidly washed with 0.5-3 times the volume of high-purity water at 5-15°C to remove metal and anionic impurities from the residual mother liquor on the crystal surface to the maximum extent. Subsequently, the solution is vacuum dried at 50-80°C to obtain electronic-grade high-purity boric acid product. By combining the above-mentioned solid-phase decomposition, zone melting refining, controlled hydration, and slow cooling crystallization, the embodiments of the present invention can significantly reduce the content of metallic impurities and non-volatile impurities in industrial-grade boric acid, thus meeting the purity requirements of boric acid for electronic applications.

[0039] Example

[0040] Industrial-grade boric acid was used as a raw material and tested, and the following results were obtained:

[0041] The mass percentage of H3BO3 is 97.5%; the mass fraction of Na is 150 μg / g; the mass fraction of K is 60 μg / g; the mass fraction of Ca is 250 μg / g; the mass fraction of Mg is 80 μg / g; the mass fraction of Fe is 120 μg / g; the mass fraction of Al is 70 μg / g; the mass fraction of Pb is 20 μg / g; and the mass fraction of Cl is... - The mass fraction is 80 μg / g; the mass fraction of sulfate ions is 120 μg / g.

[0042] Weigh 1000g of industrial-grade boric acid and place it into the central quartz boat of a quartz tube furnace with an inner diameter of 80mm and a length of 1200mm. Set up three independent temperature control zones along the material axis, with each zone being 400mm long. Introduce argon gas at a flow rate of 0.8L / min and adjust the furnace pressure to 50kPa.

[0043] Heat up according to the following procedure:

[0044] 1) The first temperature zone is raised to 100℃ and held for 1 hour to remove free water;

[0045] 2) The second temperature zone is raised to 170℃ and held for 2 hours to gradually remove water of crystallization;

[0046] 3) The third temperature zone is raised to 280℃ and kept at that temperature for 4 hours to allow boric acid to completely decompose into boron trioxide.

[0047] Throughout the heating and holding process, the generated water vapor and volatile impurities were continuously discharged through the condenser and gas outlet connected to the tail of the furnace. It was observed that the material gradually changed from a white powder to a transparent viscous melt. After the surface bubbles were significantly reduced, the mixture was kept for 30 minutes to obtain a clear boron trioxide melt.

[0048] The aforementioned boron trioxide melt was poured into a polished stainless steel crystallizing mold through a high-temperature corrosion-resistant funnel under argon protection. The crystallizing mold has an inner diameter of 60 mm and a total length of 600 mm, with a length-to-diameter ratio of 10:1. The crystallizing mold is fitted with an electric heating belt and a water-cooling jacket. The bottom water-cooling jacket is connected to a low-temperature circulating water system, and the top electric heating belt is connected to a temperature controller.

[0049] After casting, maintain the top temperature at 280℃ while simultaneously turning on the bottom water cooler to create an axial temperature gradient from bottom to top inside the crystallization mold. Control the cooling rate to ensure the solid-liquid interface advances uniformly from the bottom to the top of the mold until the melt is completely solidified, resulting in a boron trioxide ingot with macroscopic internal connectivity and a length of approximately 550mm.

[0050] Remove the boron trioxide ingot, trim both ends axially to make the end faces flat, and install it coaxially with the quartz support tube of the zone melting furnace. Place the ingot vertically into the zone melting furnace, introduce argon gas with a purity of 99.999%, adjust the furnace pressure to 30 kPa, and maintain the argon gas flow rate at 0.5 L / min.

[0051] A narrow melting zone of approximately 6 mm width is established in the middle of the ingot using a ring-shaped high-frequency heater. The melting zone is moved upwards from the bottom of the ingot at a speed of 2 mm / min, completing one bottom-up zone melting cycle. Then, the melting zone is moved downwards at the same speed, completing one top-down zone melting cycle. This zone melting refining process is repeated six times. The termination position of the melting zone is recorded after each melting cycle for reference in subsequent shearing.

[0052] After the zone melting is completed and the ingot is naturally cooled to room temperature, the ingot is divided into three sections from bottom to top in a length ratio of 10%:80%:10%. The bottom 10% section and the top 10% section are cut off, and the middle 80% section is reserved as a high-purity boron trioxide middle section.

[0053] High-purity boron trioxide is partially crushed, coarsely crushed using a jaw crusher, and then finely crushed using a roller crusher. After screening, particles with a diameter of 0.5-3mm are obtained. 800g of these particles are weighed and loaded into a vertical cylindrical stainless steel hydration reactor with a diameter of 100mm and a height of 800mm. Three sets of annular spray pipes are evenly arranged along the height direction on the inner wall of the reactor. Each set of spray pipes has 24 spray holes with a diameter of 0.8mm.

[0054] High-purity nitrogen gas was introduced into the reactor and purged for 10 minutes before stopping. High-purity water with a conductivity of no more than 0.1 μS / cm was then introduced into the metering pump connected to the spray pipe, and the reactor jacket was heated to 50°C.

[0055] The metering pump is turned on, and the solution is sprayed from top to bottom at an initial flow rate of 2 BV / h (the volume of high-purity water is twice the volume of the aggregated particles per hour). A filter plate is installed at the bottom to collect the sprayed liquid. The conductivity and refractive index of the effluent are monitored in real time by an online conductivity meter and a refractive index sensor installed on the effluent pipeline. When either parameter reaches the preset upper limit value, the spray flow rate is reduced to 1 BV / h. If the parameter returns to the set range, the flow rate is restored to 2 BV / h.

[0056] Under the above conditions, hydration was continuously sprayed for 6 hours. During this period, liquid samples were taken every hour to measure the boric acid concentration, confirming that the solution was close to saturation and that there was no large amount of spontaneous crystallization. After hydration, spraying was stopped, and the solution was allowed to stand for 10 minutes. The high-purity boric acid solution at the bottom of the reactor was drained, and the volume was recorded as the hydration liquid.

[0057] Open the top of the reactor and pour out all the wet particles. After sieving to remove any possible agglomerates, weigh the particles and calculate the proportion of residual boron trioxide mass to the initial amount added. If the residual proportion is greater than 1%, put the batch of particles back into the reactor and continue spraying hydration for 3 hours under the above conditions. Separate the solution and particles again until the residual proportion is less than 1%. Combine the high-purity boric acid solutions obtained from each hydration, filter to remove insoluble matter, and obtain a transparent and clear high-purity boric acid solution.

[0058] The high-purity boric acid solution was transferred to a jacketed glass crystallizer equipped with a stirrer. The initial temperature was measured to be 70℃, corresponding to a boric acid concentration slightly lower than the saturation concentration. The stirrer was turned on at 100 rpm, and the temperature was first lowered to 55℃ (slightly above the saturation temperature) at a rate of 2℃ / h, and maintained at this temperature for 1 hour. Then, the cooling rate was adjusted to 0.5℃ / h, and the temperature was continuously lowered to 10℃. At the beginning of the cooling process, 0.5% (by mass) of high-purity boric acid seed crystals with a particle size of approximately 0.3-0.5 mm were added.

[0059] After crystallization, stop cooling and stirring, let stand for 1 hour, and then separate the crystals from the mother liquor using a centrifuge to obtain wet boric acid crystals. Immediately wash the wet crystals with high-purity water at 8°C, using twice the volume of the crystals, for no more than 3 minutes. Discard the washing solution.

[0060] The washed wet crystals were spread on a stainless steel tray and placed in a vacuum drying oven. They were dried at 70°C and a vacuum of less than -0.09 MPa for 8 hours and then cooled to room temperature to obtain electronic-grade high-purity boric acid.

[0061] Comparative Example 1

[0062] The difference between this comparative example and the embodiment is that: instead of zone melting refining, the entire ingot is directly crushed, and after coarse crushing, it is crushed and screened to obtain boron trioxide particles with a particle size of 0.5-3mm. 800g of these particles are weighed out for subsequent hydration.

[0063] Comparative Example 2

[0064] The difference between this comparative example and the embodiment is that the complete dissolution method is used instead of spray hydration and saturation control.

[0065] The complete dissolution method involves crushing high-purity boron trioxide to a particle size of 0.5-3 mm and then directly adding it to a certain volume of high-purity water. The mixture is stirred at 60°C until the boron trioxide is completely dissolved, yielding a transparent boric acid solution. No spraying is used in this process, and the boric acid concentration is maintained at the conventional excess water dissolution state.

[0066] The experimental results are shown in Tables 1 and 2.

[0067] 1. Sample numbering and sample preparation

[0068] 1) Sample number

[0069] Industrial-grade boric acid raw material in the examples: denoted as Sample A; electronic-grade high-purity boric acid prepared according to the process in the examples: denoted as Sample B; product of Comparative Example 1: denoted as Sample C; product of Comparative Example 2: denoted as Sample D.

[0070] 2) Sample preparation

[0071] Each sample was lightly ground under clean conditions and passed through a 200-mesh sieve to remove obvious lumps; it was then dried in a vacuum drying oven at 60°C for 2 hours, cooled to room temperature, and sealed for later use.

[0072] 2. Determination of H3BO3 main content

[0073] The mass fraction of boric acid was determined by acid-base titration.

[0074] 1) Reagents and solutions

[0075] Sodium hydroxide standard solution, c(NaOH)≈0.1mol / L, accurately calibrated;

[0076] A standard hydrochloric acid solution, c(HCl)≈0.1mol / L, is used for calibration;

[0077] Methyl red indicator solution.

[0078] 2) Measurement steps

[0079] Accurately weigh approximately 0.2000 g of the sample and record the mass m; dissolve the sample in approximately 100 mL of deionized water after carbon dioxide removal treatment, and adjust the temperature to (25±1)℃; add an appropriate amount of methyl red indicator and titrate with sodium hydroxide standard solution to the endpoint; record the volume consumed V, and correct according to the blank test results; calculate the mass fraction of H3BO3 in the sample according to the stoichiometric relationship of the neutralization reaction between boric acid and sodium hydroxide. Each sample is measured in triplicate, and the average value is taken as the result.

[0080] 3. Determination of metallic impurity elements

[0081] Metallic impurities such as Na, K, Ca, Mg, Fe, Al, and Pb were determined using inductively coupled plasma mass spectrometry (ICP-MS).

[0082] 1) Sample digestion

[0083] Accurately weigh approximately 0.1000 g of the sample into a polytetrafluoroethylene digestion vessel; add 2 mL of ultrapure nitric acid and 8 mL of ultrapure water, and perform programmed temperature digestion in a microwave digester (maximum temperature 180℃, hold for 30 min); after digestion and cooling, transfer to a 50 mL volumetric flask, dilute to the mark, mix well and set aside.

[0084] 2) Instrument conditions

[0085] ICP-MS was operated under recommended operating conditions, and quantification was performed using the external standard curve method. Multi-element mixed standard solutions were prepared with a concentration range covering the expected sample content. Method blanks and quality control samples were inserted into each batch of samples to correct for instrument drift.

[0086] 3) Results Processing

[0087] The test results were converted to μg / g (mass fraction), and each sample was measured twice in parallel, and the average value was taken.

[0088] 4. Determination of anionic impurities (Cl) - SO4 2- )

[0089] Determination of Cl by ion chromatography - and sulfate ions.

[0090] 1) Sample dissolution

[0091] Weigh approximately 0.1000 g of the sample into a 100 mL volumetric flask, dissolve it in ultrapure water and dilute to the mark, mix well; filter through a 0.22 μm filter membrane to remove trace amounts of insoluble matter.

[0092] 2) Ion chromatography conditions

[0093] Suppressed anion exchange column;

[0094] The eluent is a mixed solution of carbonate and bicarbonate, with a flow rate of approximately 1.0 mL / min;

[0095] The conductivity detector operates in suppression mode.

[0096] Use Cl - and SO4 2- A series of standard solutions were prepared to establish a calibration curve. Detection results were converted to μg / g mass fraction.

[0097] 5. TOC and conductivity measurement

[0098] 1) TOC (Total Organic Carbon)

[0099] According to the TOC analyzer operating procedure, take the sample and prepare an aqueous solution of a certain concentration (e.g., 10 g / L), and determine the TOC value in ppb; each sample is measured twice and the average is taken.

[0100] 2) Conductivity

[0101] A certain mass of sample was prepared into a 10 g / L boric acid aqueous solution, and the conductivity was measured at (25±1)℃ using a conductivity meter. The unit was μS / cm. Each sample was measured twice, and the average value was taken.

[0102] 6. Determination of insoluble matter content

[0103] 1) Weigh approximately 5,000 g of the sample into a beaker, add a certain amount of high-purity water (e.g., 100 mL), and stir in a 60°C water bath until basically dissolved;

[0104] 2) Filter the solution through a pre-weighed 0.45μm filter membrane, and dry the filter membrane and residue in a vacuum drying oven at 60℃ until constant weight;

[0105] 3) Weigh the dried filter membrane, subtract the mass of the blank filter membrane, and obtain the mass of insoluble matter, which is then converted to mg / kg.

[0106] Table 1. Detection results of main content and metallic impurities

[0107] Table 2 Results of anionic impurities, TOC, insoluble matter, and conductivity

[0108] As can be seen from Table 1, the mass fraction of metallic impurities such as Na, Ca, and Fe in industrial-grade boric acid raw materials is around 10%. 2In Comparative Example 1, without zone refining, although impurities were reduced through hydration and crystallization steps, elements such as Na, Ca, and Fe remained at several μg / g levels, significantly higher than in the product of the Example. This demonstrates that zone refining plays a crucial role in the deep removal of metallic impurities. The levels were on the order of μg / g. After processing in this embodiment, all metallic impurities in the product were reduced to below 1 μg / g, and the main content increased from 97.5% to 99.999%.

[0109] Comparative Example 2, under the same zone melting refining conditions, only employed complete dissolution in the hydration stage, without utilizing spray hydration and near-saturation control combined with solid-phase circulation. As a result, some soluble metal impurities remaining in boron trioxide after zone melting were completely dissolved and entered the solution during the dissolution process. This resulted in residual levels of elements such as Na and Ca being between those of Example 1 and Comparative Example 1. This demonstrates that the strategy of preferentially retaining impurities in incompletely hydrated particles through spray hydration and solution concentration control can further reduce soluble impurities after zone melting.

[0110] As can be seen from Table 2, in the products of the examples, Cl - With sulfate ion mass fraction lower than that of industrial grade raw materials and comparative samples, the conductivity of the 10 g / L solution dropped to below 1 μS / cm, and the insoluble content was also significantly reduced. This indicates that the operation of removing volatile impurities through multi-temperature zone thermal decomposition, removing non-volatile impurities through directional solidification and zone melting refining, and slow cooling crystallization combined with rapid washing with low-temperature high-purity water effectively controls anionic impurities and insoluble matter, meeting the requirements of electronic-grade applications for conductivity and cleanliness.

[0111] The results in Tables 1 and 2 show that, under the premise of a simple process flow and limited reagent types, this embodiment achieves multi-level reduction of metallic impurities, anionic impurities, and insoluble particles through solid-phase zone melting refining, spray hydration and concentration feedback, slow cooling crystallization and low-temperature washing. Compared with the approach of only using thermal decomposition, recrystallization or zone melting, complete dissolution and crystallization, it can stably obtain high-purity boric acid products that meet the requirements of electronic grade indicators.

[0112] In the description of this invention, it should be understood that the terms "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, and are only for the convenience of describing this invention, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention.

[0113] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing electronic-grade high-purity boric acid, characterized in that, Includes the following steps: (1) Industrial grade boric acid is heated in a tube furnace with multiple temperature zones. Free water is removed in the first temperature zone at 80-140℃, dehydration is carried out in stages in the second temperature zone at 140℃-220℃, and the temperature is maintained in the third temperature zone at 220℃-360℃ for 2-8 hours to obtain boron trioxide melt. (2) The boron trioxide melt is poured into a crystallization mold with a horizontal temperature gradient under an inert atmosphere and cooled directionally from one end to the other to obtain a boron trioxide ingot. (3) Place the boron trioxide ingot in a vertically arranged zone melting furnace, and form a narrow melting zone in the ingot by a ring heater that moves back and forth along the ingot axis. Move the melting zone from one end of the ingot to the other end at a speed of 0.5-10 mm / min to complete 2-10 reciprocating zone melting refining to obtain the high-purity boron trioxide mid-section after zone melting refining. (4) The high-purity boron trioxide middle section is crushed into particles with a particle size of 0.5-10 mm and added to a hydration reactor with an internal surface spray structure. Under the condition of 30-80℃, high-purity water is sprayed, the hydration reaction time is controlled to be 1-10 hours, and the boric acid concentration in the solution is controlled to be saturated by adjusting the spray flow rate and hydration temperature, so as to obtain a mixed system of high-purity boric acid solution and incompletely hydrated particles; (5) Perform solid-liquid separation on the mixed system formed in step (4), recover the high-purity boric acid solution, return the incompletely hydrated boron trioxide particles to step (4) for further hydration until the residual rate is lower than the predetermined mass fraction, and combine the high-purity boric acid solutions obtained from multiple cycles to obtain the target high-purity boric acid solution. (6) The high-purity boric acid solution is slowly cooled and crystallized under stirring. The final cooling temperature is controlled at 5℃-25℃. Boric acid crystals are precipitated, separated by centrifugation or filtration, and then quickly washed with high-purity water. The solution is then vacuum dried at 50℃-80℃ to obtain electronic-grade high-purity boric acid product.

2. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, The industrial-grade boric acid in step (1) contains 95% to 99.5% H3BO3 by mass.

3. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, In step (1), the temperature control of each temperature zone of the tubular furnace is as follows: the temperature of the first temperature zone is 90-120℃, the temperature of the second temperature zone is 150-190℃, and the temperature of the third temperature zone is 260-320℃. Step (1) is carried out under the protection of argon or nitrogen.

4. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, In step (2), the crystallization mold is made of stainless steel or high-purity quartz with polished inner wall. The ratio of mold length to diameter is 5-20:

1. During directional cooling, a cold end is set at the bottom of the mold and a hot end is set at the top of the mold, so that the solid-liquid interface is pushed unidirectionally from the bottom to the top of the mold.

5. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, In step (3), the zone melting refining process is carried out under a low-pressure inert atmosphere, and the pressure inside the zone melting furnace is controlled at 10-90 kPa.

6. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, The number of reciprocating cycles in the zone melting refining step (3) is set according to the initial content of metal impurities in the industrial-grade boric acid. For raw materials with a metal impurity mass fraction in the range of 100-1000 μg / g, the number of reciprocating cycles in the zone melting is 4-8 times.

7. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, The residual rate of incompletely hydrated boron trioxide particles in step (5) is determined by online quality monitoring or intermittent sampling and weighing. When the mass fraction of residual boron trioxide is less than 1% of the initial amount added, the cyclic hydration of the current batch of particles is stopped.

8. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, In step (6), slow cooling crystallization is carried out in stages. First, the temperature is lowered to near the saturation temperature at a rate of 1℃-3℃ per hour in the range above the saturation temperature of boric acid. Then, the temperature is lowered to the final temperature at a rate of 0.2-1℃ per hour. At the beginning of cooling, 0.1-1.0% of high-purity boric acid crystals by mass of the solution are added as seed crystals.

9. The method for preparing electronic-grade high-purity boric acid according to claim 1, characterized in that, In step (6), high-purity water is used for washing at low temperature. The washing water temperature is controlled at 5-15℃, and the volume of washing water for each batch of boric acid crystals is 0.5-3 times the volume of the crystals.

10. A high-purity boric acid, obtained by the preparation method of electronic-grade high-purity boric acid as described in any one of claims 1-9.